Cyclorotation during femtosecond laser–assisted cataract surgery measured using iris registration. Issue 7 (July 2017) - Hummel, Chad D.; Diakonis, Vasilios F.; Desai, Neel R.; Arana, Allen; Weinstock, Robert J.
Abstract : Purpose : To assess ocular cyclorotation of eyes having femtosecond laser–assisted cataract surgery using iris registration. Setting : Eye Institute of West Florida, Largo, Florida, USA. Design : Retrospective cases series. Methods : Charts of patients who had femtosecond laser–assisted cataract surgery with preoperative and intraoperative iris registration in 1 or 2 eyes between November 2015 and March 2016 were reviewed. Cyclorotation was assessed via iris‐registration acquired preoperatively using the Cassini topographer (patient in upright position) and intraoperatively using the iris registration option of the Lensar laser system (patient in supine position) acquired immediately before the laser treatment. Results : The study comprised 241 patients (337 eyes). The mean age of the 107 men and 134 women was 68.0 years ± 9.0 (SD) (range 37 to 90 years). The mean absolute value of cyclorotation was 5.81 ± 4.20 degrees (range 0 to 17 degrees), which was statistically significant when comparing the preoperative axis with the intraoperative axis deviation ( P < .0001). Overall, incyclorotation (67.4%) was more common than excyclorotation (30.9%). In patients having bilateral femtosecond laser–assisted cataract surgery, bilateral incyclorotation (47.37%) was the most common occurrence. Conclusions : During femtosecond laser–assisted cataract surgery, clinically significant cyclotorsion that might influence astigmatism correction outcomes can occur in patients having cataract extraction. Iris registration was useful in accounting for cyclorotation during this procedure when corneal or intraocular lens–based forms of astigmatic corrections will be used.